Emotional interference under low versus high executive control. (25th April 2019) - Grützmann, Rosa; Riesel, Anja; Kaufmann, Christian; Kathmann, Norbert; Heinzel, Stephan
Abstract: Previous research has demonstrated that task‐irrelevant emotional distractors interfere with task performance especially under low phasic executive control (i.e., in nonconflict trials). In the present study, we measured medio‐frontal ERPs (N2 and correct‐related negativity, CRN) to elucidate which aspects of task performance are affected by emotional interference in a flanker task. To create emotional interference, negative and neutral pictures were presented during the flanker stimuli. N2 and CRN were reduced after negative pictures, indicating that conflict processing and performance monitoring are both affected by emotional interference. On the behavioral level, prolonged response times after negative pictures were observed under low phasic executive control (i.e., in compatible trials). Additionally, we explored whether emotional interference is modulated not only by phasic changes in executive control (i.e., conflict vs. nonconflict trials) but also by tonic changes in executive control (i.e., low vs. high overall conflict frequency). To this end, the flanker task consisted of two blocks with 25% versus 75% incompatible trials. Prolonged response times after negative pictures in compatible trials were observed only under low tonic executive control but not under high executive control. Abstract : Task‐irrelevant emotional distractors interfere with task performance but this effect is reduced in trials with high phasic executive control. In the present study we investigated the effect of tonic executive control on emotional interference. Behavioral emotional interference was only present under low tonic executive control but not under high tonic executive control, indicating that tonic executive control provides a similar protective effect as phasic executive control. Furthermore, using event‐related potentials (N2, CRN) we investigated which aspects of task performance are affected by emotional interference. We found that stimulus‐related (N2) and response‐related (CRN) processing were both reduced after emotional distractors.